2014
DOI: 10.1249/mss.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Does Hydrotherapy Help or Hinder Adaptation to Training in Competitive Cyclists?

Abstract: Although some effects of CWI on performance were unclear, data from this study do not support recent speculation that CWI is detrimental to performance after increased training load in competitive cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
(30 reference statements)
6
36
1
1
Order By: Relevance
“…Yamane et al (2006) reported that one leg post-exercise CWI over 4 to 6 weeks of training attenuated cycling performance improvements when compared to the control leg (no CWI). Conversely, Halson et al (2014) found that post-exercise CWI four times per week over 3 weeks of intensified training, followed by taper, did not impair adaptation to training in competitive cyclists. Instead, the CWI group demonstrated a marginal (non-significant) increase in performance when compared with the control group.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Yamane et al (2006) reported that one leg post-exercise CWI over 4 to 6 weeks of training attenuated cycling performance improvements when compared to the control leg (no CWI). Conversely, Halson et al (2014) found that post-exercise CWI four times per week over 3 weeks of intensified training, followed by taper, did not impair adaptation to training in competitive cyclists. Instead, the CWI group demonstrated a marginal (non-significant) increase in performance when compared with the control group.…”
Section: Introductionmentioning
confidence: 86%
“…Only few studies have evaluated the effect of CWI during endurance training (Yamane et al 2006;Halson et al 2014;Ihsan et al 2015) and the results are not consistent. Yamane et al (2006) reported that one leg post-exercise CWI over 4 to 6 weeks of training attenuated cycling performance improvements when compared to the control leg (no CWI).…”
Section: Introductionmentioning
confidence: 99%
“…3 If an athlete is better recovered between training sessions, subsequent training quality, volume or intensity may improve, potentially serving as a stimulus to enhance long-term training adaptations. 4 Water immersion is widely used by athletes in an attempt to expedite the recovery process following training and/or competition. 5 Although the mechanisms for improvement are largely unknown, both cold water immersion (CWI; ≤ 20°C) and contrast water therapy (CWT; alternating between hot (≥ 36°C) and cold water) have been reported to improve recovery from a variety of exercise modes.…”
Section: Introductionmentioning
confidence: 99%
“…Kelelahan-kelelahan yang terjadi pada atlet tersebut harus diatasi, salah satu caranya dengan terapi yang menggunakan air sebagai medianya dikenal dengan nama Hydrotheraphy (Halson et al, 2014;Stanley, Buchheit, & Peake, 2012;Vaile, Halson, Gill, & Dawson, 2008). "penggunaan air baik dalam wujud cair, larutan, dan uap dalam terapi melawan penyakit, trauma dan massage (pijatan) dinamakan Hydromassage.…”
Section: Pendahuluanunclassified